Christianity in China: Acculturation and Adjustment from a Critical Perspective - Qing, Yang Guo (Numen, 2026)
This article explores the historical process of the sinicization of Christianity from the perspective of frame alignment theory, revealing the processes, strategies, and transformations involved in the development of Christianity in China. The sinicization of Christianity is essentially a process of acculturation in order to eliminate the tension between Christianity and Chinese society. The sinicization of Nestorianism in the Tang dynasty, the sinicization of the Jesuit Order in the Ming and Qing dynasties, the vernacularization of Christianity in the late Qing dynasty and the Republic of China, and the adaptation of Chinese Christianity after the founding of New China are considered as processes of bridging, amplification, extension and transformation in the sinicization of Christianity. Through these processes, Christianity has realized the transformation from "Christianity in China" to "Chinese Christianity," and has reached a certain degree of acceptance and toleration within Chinese society.